Policing same-sex relations in eighteenth-century Paris: archival voices from 1785 - Merrick, Jeffrey (The Pennsylvania State University Press, 2024)
Police in Paris arrested thousands of men for sodomy or similar acts in the eighteenth century. In the mid-1780s, they recorded depositions in which prisoners recounted their own sexual histories. These remarkable documents, curated and translated into English by Jeffrey Merrick, allow us to hear the voices of men who desired men and to explore complex questions about sources, patterns, and meanings in the history of sexuality. This volume centers on two cartons of paperwork from commissaire Charles Convers Desormeaux. Dated from 1785, the cartons contain 221 dossiers of men arrested for sodomy or similar acts in Paris. Merrick translates and annotates the police interviews from these dossiers, revealing how the police and those they arrested understood sex between men at the time. Merrick discusses the implications of what the men said (and what they did not say), how they said it, and in what contexts it was said. The best-known works of clergy and jurists, of enemies and advocates of Enlightenment, and of novelists and satirists from the eighteenth century tell us nothing at all about the lived experience of men who desired men. In these police dossiers, Merrick allows them to speak in their own words. This primary text brings together a wealth of important information that will appeal to scholars, students, and general readers interested in the history of sexuality, sodomy, and sexual policing.